Nano-sized Soluplus® polymeric micelles enhance the induction of tetanus toxin neutralising antibody response following transcutaneous immunisation with tetanus toxoid. Issue 18 (25th April 2017) - Saydam, Manolya; Cheng, Woei Ping; Palmer, Nathan; Tierney, Robert; Francis, Robert; MacLellan-Gibson, Kirsty; Khan, Ambreen; Mawas, Fatme
Highlights: Tetanus toxoid (TTxd) is poorly immunogenic in transcutaneous immunisation (TCI). TCI with TTxd-Soluplus® increased the tetanus toxin neutralising antibody response. Soluplus® enhanced the uptake of TTxd through the skin dermis and epidermis. Abstract: The use of Soluplus® polymeric micelles as a novel adjuvant for tetanus toxoid (TTxd) in transcutaneous immunisation was evaluated. TTxd was added to Soluplus® polymeric micelles to form TTxd-Soluplus® nano-aggregates with a size of 68 nm. Non-adjuvanted TTxd commonly induces very poor antibody response by the transcutaneous route. However, in this study, the use of TTxd-Soluplus® resulted in a significant increase in the antibody response to TTxd, which was similar to that induced in the presence of CPG-oligodeoxynucleotides (CPG-ODNs) adjuvant. The toxin neutralising potency of the immune sera induced by TTxd-Soluplus® was also much stronger than that from TTxd alone, in a passive transfer experiment in mice. Soluplus® also enhanced the immunogenicity of the toxoid when TTxd-Soluplus® was stored at 4 °C for 4 weeks, but not at higher temperatures. Confocal microscopy imaging showed a much higher uptake of TTxd in the epidermis and dermis layers of the skin when it was associated with Soluplus®, suggesting that the mechanism for Soluplus® adjuvanticity is through enhanced uptake of the TTxd through the skin. Overall, our findings demonstrated that Soluplus® is an effective novel adjuvant for transcutaneous immunisation.